2003
DOI: 10.1177/003172170308500208
|View full text |Cite
|
Sign up to set email alerts
|

Apprenticing Adolescents to Reading in Subject-Area Classrooms

Abstract: ESPITE THE increasing pressures for content coverage in the current high-stakes testing environment, a small but growing number of middle and high school teachers across the country are taking the time to teach about reading in their disciplines. They are learning to recognize their own complex disciplinespecific reading processes and are helping their students do the same, implementing an approach we call Reading Apprenticeship.® These teachers' efforts have made a significant difference in attitudes and outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…The concept of metacognition refers to one's knowledge about one's cognitive processes or anything related to those processes (Flavell, 1976, Brown, Bransford, Ferrara & Campione, 1983Paris, 1988, Hudson 2007. In metacognitive conversation, teacher and students discuss their personal relationships to reading in the discipline, the cognitive strategies they use to solve comprehension problems, the structure and language of particular types of texts, and the kinds of knowledge required to make sense of reading materials (Schoenbach, Braunger, Greenleaf, & Litman, 2003). Through metacognition, apprentice readers begin to become aware of their reading processes (Paris & Jacobs 1984).…”
Section: The Personal Dimension Involves Addressing Adolescents' Intementioning
confidence: 99%
See 1 more Smart Citation
“…The concept of metacognition refers to one's knowledge about one's cognitive processes or anything related to those processes (Flavell, 1976, Brown, Bransford, Ferrara & Campione, 1983Paris, 1988, Hudson 2007. In metacognitive conversation, teacher and students discuss their personal relationships to reading in the discipline, the cognitive strategies they use to solve comprehension problems, the structure and language of particular types of texts, and the kinds of knowledge required to make sense of reading materials (Schoenbach, Braunger, Greenleaf, & Litman, 2003). Through metacognition, apprentice readers begin to become aware of their reading processes (Paris & Jacobs 1984).…”
Section: The Personal Dimension Involves Addressing Adolescents' Intementioning
confidence: 99%
“…What is more, working in small groups, benefiting from a second level of apprenticeship, thinking together and having constant access to a model (either the teacher or the better reader of the group), made learners' reading processes visible to themselves and to each other; and finally with direct strategy instruction, gradual removal of scaffolding and learners' growing confidence, learners at different proficiency levels became more capable of handling authentic texts and more enabled to "break the code" (Schoenbach, Braunger, Greenleaf, & Litman, 2003) of academic language.…”
Section: Providing Scaffoldingmentioning
confidence: 99%
“…Teachers who have limited investment in class reading often are reliant on a single textbook for instruction that can be either uninteresting or written above grade level (Allington, 2002;Daniels & Zemelman, 2004;Wilhelm, 2007). Additionally, the dual limitations of limited class time and the necessity of covering mandated curriculum standards have both impacted content teachers' ability to support class reading (Fisher, 2004;Ness, 2007;Schoenbach, Braunger, Greenleaf, & Litman, 2003). Ness (2007) collected data in eight middle and high school science and social studies classrooms and concluded students experienced little direct exposure to print in the classes she observed.…”
Section: The Link Between Student Reading Attitudes and Teacher Instrmentioning
confidence: 99%
“…These strategies are "procedural, purposeful, effortful, willful, essential, and facilitative in nature" (Jetton & Alexander, 2001, ¶ 17). Highlighting a set of instructional strategies called Reading Apprentice, Schoenbach, Braunger, Greenleaf, and Litman (2003) suggested that effective strategies focus on "how we read and why we read in the ways we do" (p. 134). In CTE, this translates into reading different genre of texts using different strategies and helping students understand the purposes for reading in a specific way.…”
Section: Instruction With Content Area Reading Strategiesmentioning
confidence: 99%